ABOUT CARDIOLOGY AND LIFE: INTERVIEW WITH AN INTERESTING CHARACTER MEDICATION SHOULD BE A PART OF THE HUMAN ORGANISM (INTERVIEW WITH E.I. CHAZOV) - N. V. Dolgushina (Рациональная фармакотерапия в кардиологии)
.